Empresses, religious practice and the imperial image in Ming China: the ordination scroll of Empress Zhang (1493) - Luk, Y; Luk Yu Ping (2010)
The Ordination Scroll of Empress Zhang (1493) in the San Diego Museum of Art, a highlight at the Taoism and the Arts of China exhibition in 2000, is an unusual object among surviving visual material from Ming dynasty China (1368 – 1644). At over twenty-seven metres long, the scroll contains meticulously painted images and a detailed inscription that records the Daoist ordination of Empress Zhang (1470 – 1541), consort of the Hongzhi emperor (r. 1488 – 1505) by the Orthodox Unity institution. The event it documents, which elevates the empress into the celestial realm, would be unknown to history if not for the survival of this scroll. This dissertation is an in-depth study of the Ordination Scroll that also considers its implications for understanding the activities of empresses and their representations during the Ming dynasty. The first three chapters of this dissertation closely examine the material, visual and textual aspects of the Ordination Scroll. The remaining two chapters situate the scroll within the broader activities of Ming empresses. A complete translation of the main inscription in the scroll is provided in the appendix.